Endogenous Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Plays a Protective Effect Against Noise-Induced Hearing Loss - Ruel, Jérôme; Guitton, Matthieu J.; Gratias, Paul; Lenoir, Marc; Shen, Sanbing; Puel, Jean-Luc; Brabet, Philippe; Wang, Jing (Frontiers in Cellular Neuroscience, 2021)
Pituitary adenylyl cyclase-activating polypeptide (PACAP) is a member of the vasoactive intestinal polypeptide (VIP)-secretin-glucagon family of neuropeptides. They act through two classes of receptors: PACAP type 1 (PAC1) and type 2 (VPAC1 and VPAC2). Among their pleiotropic effects throughout the body, PACAP functions as neuromodulators and neuroprotectors, rescuing neurons from apoptosis, mostly through the PAC1 receptor. To explore the potential protective effect of endogenous PACAP against noise-induced hearing loss, we used a knockout mouse model lacking PAC1 receptor expression (PACR1-/-) and a transgenic humanized mouse model expressing the human PAC1 receptor (TgHPAC1R). Based on complementary approaches combining electrophysiological, histochemical and molecular biological evaluations, we show PAC1R expression in both afferent and efferent neurons and in cochlear apical cells of the organ of Corti. Wild-type (WT), PAC1R-/-, and TgHPAC1R mice exhibit similar auditory thresholds. For most of the frequencies tested after acute noise damage, however, PAC1R-/- mice showed a larger elevation of auditory threshold than did their WT counterparts. By contrast, in a transgene copy numbers-dependent fashion, TgHPAC1R mice showed smaller noise-induced elevations of auditory thresholds compared to their WT counterparts. Together, these findings suggest that PACAP could be a candidate for endogenous protection against noise-induced hearing loss.